New euophryine jumping spiders from Southeast Asia and Africa (Araneae: Salticidae: Euophryinae) - Zhang, Jun-Xia; Maddison, Wayne P. (Zootaxa, 2012)
Sixteen new species and four new genera of euophryine jumping spiders from the Old World (China, Malaysia and SouthAfrica) are described. The new genera are Chinophrys gen. nov. (type species C. pengi sp. nov.), Foliabitus gen. nov.(type species F. longzhou sp. nov.), Parabathippus gen. nov. (type species Bathippus shelfordi Peckham & Peckham, andnew species P. cuspidatus sp. nov., P. kiabau sp. nov., P. magnus sp. nov.) and Parvattus gen. nov. (type species P. zhui sp.nov.). The other new species belong to the genera Colyttus Thorell, 1891 (C. robustus sp. nov.), Emathis Simon, 1899 (E.gombak sp. nov.), Lagnus L. Koch, 1879 (L. edwardsi sp. nov.), Laufeia Simon, 1889 (L. concava sp. nov. and L. eximiasp. nov.), Thiania C. L. Koch, 1846 (T. latibola sp. nov. and T. tenuis sp. nov.) and Thyenula Simon, 1902 (T. laxa sp. nov.,T. nelshoogte sp. nov. and T. wesolowskae sp. nov.). The following species from Southeast Asia once described as Bathip-pus Thorell, 1892 are transferred to Parabathippus gen. nov.: Bathippus birmanicus Thorell, B. digitalis Zhang, Song &Li, B. macilentus Thorell, B. petrae Prószyński & Deeleman-Reinhold, B. rectus Zhang, Song & Li, B. sedatus Peckham& Peckham and B. shelfordi Peckham & Peckham. Laufeia liujiapingensis Yang & Tang is transferred to Chinophrys gen.nov.. Laufeia scutigeraŻabka is transferred to Foliabitus gen. nov.. Diagnostic illustrations are provided for all of the described new species. Photographs of living spiders are also provided for some new species.